2019
DOI: 10.3127/ajis.v23i0.1816
|View full text |Cite
|
Sign up to set email alerts
|

Tele-monitoring Technology as a Tool for Monitoring and Management of Patients with Congestive Heart Failure

Abstract: Telehealth interventions are designed to facilitate the remote exchange of information and data between patients and health care providers, improving the quality and safety of the patients and increasing efficiency and cost-effectiveness of health care providers. The development of telecommunications and virtual technology allowed a number of telehealth systems to be applied in different health care areas. These technologies can provide an alternative monitoring and solutions for decreasing the hospital readmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…Participants valued the integration of video-based features in digital interventions, whether as a visual aid for rehabilitative exercises or to facilitate remote telemedicine consultations. Our findings support the growing popularity of video-based consultations reported in other areas of global health and social care [42][43][44], with participants reporting feelings of connectedness, empowerment, and reassurance through imageand video-based sharing [45][46][47]. The incorporation of video call features within digital health technology is gaining attention, particularly as a consequence of the global COVID-19 pandemic [43,48].…”
Section: Principal Findingssupporting
confidence: 80%
“…Participants valued the integration of video-based features in digital interventions, whether as a visual aid for rehabilitative exercises or to facilitate remote telemedicine consultations. Our findings support the growing popularity of video-based consultations reported in other areas of global health and social care [42][43][44], with participants reporting feelings of connectedness, empowerment, and reassurance through imageand video-based sharing [45][46][47]. The incorporation of video call features within digital health technology is gaining attention, particularly as a consequence of the global COVID-19 pandemic [43,48].…”
Section: Principal Findingssupporting
confidence: 80%
“…Recently, telemedicine services have expanded from providing health care services at hospitals, outpatient departments, and specialist offices, as well as between health care providers, to deliver care at patients' homes. For example, Vlahu-Gjorgievska et al [13] indicated utilizing a telemonitoring system for patients with congestive heart failure at home to improve their overall health condition, which would reduce their risk of hospitalization and rehospitalization due to its ability to empower a patient's self-care, motivation, education, and self-management. Other studies indicated that telemedicine at patients' homes provides remote health consultation, remote treatment, remote intervention, and remote assessment, which can improve patients' health conditions at low cost [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Congestive heart failure is one of the most common chronic diseases, with a significant morbidity and fatality rate (Bardhan and Thouin, 2013;Jung et al, 2019). Congestive heart failure, as the name implies, is a complex chronic condition in which the heart pumps blood poorly and thus the blood's circulating ability is reduced, leading to a range of cardiovascular disease issues such as heart attack, coronary artery disease and cardiomyopathy (Vlahu-Gjorgievska et al, 2019). This is why cardiovascular disease is the leading cause of death globally, a rising concern and a growing burden on the healthcare system as patients need frequent hospitalization (Bardhan et al, 2015;Vlahu-Gjorgievska et al, 2019) and a significant cause of social and economic repercussions on the afflicted patient (Jung et al, 2019).…”
Section: Science Mappingmentioning
confidence: 99%
“…Shuffling of a service provider raises the chances of a physician not understanding or acquiring information about a patient's medical history (Akter et al, 2013a;Green et al, 2016). Given the possibility of a lack of care continuity that would result in poor service quality and patient discontent, telehealth service providers must use exemplary data management systems to keep patient information up to date and accessible to physicians for appropriate and efficient diagnosis (Vlahu-Gjorgievska et al, 2019;. Furthermore, another crucial criterion for attaining the radical changes advocated by telehealth service providers is the preparedness and willingness of physicians to implement it (Bakshi and Tandon, 2021;Sims, 2018).…”
Section: Introductionmentioning
confidence: 99%